Cobalt‐Based Active Species Molecularly Immobilized on Carbon Nanotubes for the Oxygen Reduction Reaction. Issue 17 (16th August 2017) - Kim, Sujin; Jang, Dawoon; Lim, Joonwon; Oh, Junghoon; Kim, Sang Ouk; Park, Sungjin
Abstract: Hybrid systems in which molecule‐based active species are combined with nanoscale materials may offer valuable routes to enhance catalytic performances for electrocatalytic reactions. The development of rationally designed, cost‐effective, efficient catalysts for the oxygen reduction reaction (ORR) is a crucial challenge for applications in fuel cells and metal–air batteries. A new hybrid ORR catalyst has been synthesized through a well‐defined reaction between Co‐based organometallic molecules and N‐doped multiwalled carbon nanotubes (MWCNTs) at room temperature. The hybrid ORR catalyst shows excellent catalytic performance with an onset potential of 0.95 V [vs. the reversible hydrogen electrode (RHE)], superior durability, and good methanol tolerance. Chemical and structural characterization after many reaction cycles reveals that the Co‐based organometallic species maintained the original structure of cobalt(II) acetylacetonate with coordination to the heteroatoms of the MWCNTs. A thorough electrochemical investigation indicates that the major catalytically active site is Co−O4 −NCNT . Abstract : Off the wall : A new hybrid containing molecularly dispersed cobalt‐based organometallic molecules on nitrogen‐doped multiwalled carbon nanotubes is produced through a room‐temperature process. The hybrid shows excellent electrocatalytic activity and stability for the oxygen reduction reaction. A thorough electrochemical and structural investigation suggests that the molecular Co−O4 −N structure is the major catalytically active site.